Spectral Units Analysis of Quadrangle H05‐Hokusai on Mercury. Issue 3 (7th March 2022) - Zambon, F.; Carli, C.; Wright, J.; Rothery, D. A.; Altieri, F.; Massironi, M.; Capaccioni, F.; Cremonese, G.
Abstract: MESSENGER mission data allowed the entire surface of Mercury to be mapped at various spatial scales, from both geological and compositional stand points. Here, we present a spectral analysis of the H05‐Hokusai quadrangle, using data acquired by the MESSENGER Mercury Dual Imaging System‐Wide Angle Camera. We defined a suitable set of parameters, such as reflectance and spectral slopes, to study the spectral variation though the definition of spectral units. The determination of spectral units permits to infer the physical and compositional properties of a surface by processing several parameters simultaneously, instead of the more traditional approach of interpreting each single parameter separately. We identified 11 spectral units within H05, six large scale and five localized units. The large scale units include the northern smooth plains of Borealis Planitia. South‐western H05 is characterized by two widespread spectral units, partially overlapping intercrater plains and intermediate plains. Furthermore, we found very localized spectral units corresponding to the low‐reflectance blue material of Rachmaninoff basin and the high‐reflectance red material of Nathair Facula. We investigated the link between spectral units and compositional maps obtained by GRS and XRS, to associate compositional information to the spectral units. We found some spectral units are correlated with Mg and Al variations displayed in the elemental maps. This implies that spectral variations associated to these units are mainly linked with composition rather than terrain maturity and/or grain size effects. Plain Language Summary: H05‐Hokusai quadrangle, located on Mercury northern hemisphere, shows large spectral variations. In this paper, we analyzed the properties of H05 quadrangle considering the MESSENGER/MDIS‐Wide Angle Camera data. To study the variability of H05, we defined 11 spectral units, useful not only for the spectral analysis, but also to lay the foundation for integrating spectral and morphostratigraphic information. Finally, to better characterize the geology of this quadrangle, we compared morphostratigraphic units and spectral units. We found a good match specially for few localized spectral units in correspondence of the low reflectance material of Rachmaninoff crater, Nathair facula, crater rays and ejecta. Furthermore, in some cases, spectral variations follow the Mg and Al variations derived by XRS. This confirm the spectral variations we observed in these specific areas, are mainly dominated by composition rather then other factors, such as grain size and/or terrain maturity. Key Points: H05 analysis reveals large spectral variabilites across the quadrangle We identified 11 spectral units, six large‐scale and five local spectral units Comparison between morphostratigraphic and spectral units in some cases produce a good match